The occurrence of bird-strike on aircraft: a preliminary study / Mohd Fakhrulrazi Abdullah ...[et al.] - Abdullah, Mohd Fakhrulrazi; Alias, Ahmad Jais; Ab. Wahab, Amir Hisham; Ibrahim, Izmuddin; Harun, Ahmad Shubli (2006)
This paper is a preliminary report of an ongoing study and research of the occurrence of bird-strike on aircraft· According to statistics, almost 90% of the bird-strike happens during aircraft take-off This could be very dangerous to the aircraft, and might lead to fatal accident if the strike really damages the critical parts of the aircraft. The study involves a survey on the trend of bird-strike near airports, and factors that excites the birds to flock at certain airports. Some common preventive measures to reduce the bird-strike occurrence will be discussed, and recent advances in technology that might further improve the prevention system will be proposed. As this is only a preliminary study, a detailed study in the future should also involve the ornithologists, for us to have better understanding about the bird habits and habitats.